2022
DOI: 10.1007/s10734-021-00803-7
|View full text |Cite
|
Sign up to set email alerts
|

How do international faculty at Japanese universities view their integration?

Abstract: The purpose of the study is to explore how international faculty at Japanese universities view their integration. An exploratory study of semi-structural interviews with 40 full-time international faculty hired in Japanese universities with various backgrounds was conducted. The key findings indicate that international faculty perceived their integration as a beneficial longstanding two-way process of acquiring equality, developing engagement, and forming a feeling of attachment towards Japan. Meanwhile, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Importantly, this result points to the fact that workplace satisfaction for expatriates may be positively impacted by extra-organizational enculturation to the host culture, something to which Korean universities should apparently be paying increased attention. Interestingly, results presented thus far largely mirror recent findings presented in Chen’s (2022) qualitative study of expatriate faculty in Japan. The author concluded that expatriate faculty were seeking quality and engagement intra-organizationally, while their adjustment benefited from the development of a closer cultural affinity with Japan in their everyday lives.…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, this result points to the fact that workplace satisfaction for expatriates may be positively impacted by extra-organizational enculturation to the host culture, something to which Korean universities should apparently be paying increased attention. Interestingly, results presented thus far largely mirror recent findings presented in Chen’s (2022) qualitative study of expatriate faculty in Japan. The author concluded that expatriate faculty were seeking quality and engagement intra-organizationally, while their adjustment benefited from the development of a closer cultural affinity with Japan in their everyday lives.…”
Section: Discussionsupporting
confidence: 82%
“…Scholars have criticised the underdeveloped integrative climate in Japan (e.g. Brotherhood et al, 2019;Chen, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This was largely led by the Japanese government's flagship initiatives: the Global 30 and Top Global University projects. Studies have addressed foreign early career academics' (FECAs) challenges in Japan, such as their intercultural and marginalisation experiences (Brotherhood et al, 2019; Chen, 2022). In their challenging academic work environment, their well‐being is also important, both in itself and for their efficient performance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite globalising researcher communities, little evidence has been presented on the impact of the work environment on foreign researchers' engagement (Munene, 2014;Ortiga et al, 2019). Asian higher education institutions (HEIs) have increasingly recruited foreign researchers, such as those in China, Korea, Singapore and Japan (Huang & Welch, 2021;Kim, 2016;Ortiga et al, 2019), and there is evidence that foreign researchers experience challenges due to linguistic, cultural and managerial norms in their unfamiliar environments (Brotherhood et al, 2019;Chen, 2022;Sabharwal, 2011). In this context, HEIs' effort to be cognisant and support researchers from diverse origins is of utmost concern to better engage them in work and develop their expertise.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has unpacked FECRs' culturally oriented challenges, such as culture shock and alienation in academia, via qualitative exploratory approaches (e.g., Brotherhood et al, 2019;Chen, 2022;Sabharwal, 2011). However, little is known about what explains FECRs' work engagement from a holistic perspective of workplace conditions.…”
Section: Introductionmentioning
confidence: 99%